GAYA KOMUNIKASI MASTER OF CEREMONY (MC) DALAM MEMANDU ACARA PERNIKAHAN DI KOTA LHOKSEUMAWE - Muliya Arsy; Ade Muana Husniati; Anismar Anismar; Subhani Subhani; Muhammad Ali (Jurnal Network Media, 2026)
This study examines the communication styles used by Masters of Ceremony (MCs) in guiding wedding ceremonies in Lhokseumawe City. The background of this research is based on the increasing use of professional wedding MC services and the fact that each MC has a different communication style. These differences influence the atmosphere of the event, the comfort of the bride and groom and the guests, as well as the overall impression left after the ceremony. Therefore, this study aims to identify and describe the communication styles of Masters of Ceremony in leading wedding events in Lhokseumawe and to explore how these styles help create a warm, harmonious atmosphere and effective communication during the ceremony. This research employs a descriptive qualitative approach using interviews, observations, and documentation, and is based on Robert Norton’s communication style theory (Dominant Style, Dramatic Style, Argumentative/Contentious Style, Animated Expressive Style, Relaxed Style, Attentive Style, Open Style, and Friendly Style). The findings show that not all of Norton’s communication styles are applied by the MCs studied. Of the nine communication styles proposed by Robert Norton, only eight were found in the communication practices of MCs when hosting wedding ceremonies. This indicates that the MCs tend to adapt their communication styles to the context of the event, the audience, and their role as hosts, so that one communication style is not used because it is considered less relevant or unsuitable for the sacred and formal atmosphere of a wedding ceremony.